Efficiency of Monocyte/High-Density Lipoprotein Cholesterol Ratio Combined With Neutrophil/Lymphocyte Ratio in Predicting 28-Day Mortality in Patients With Sepsis - Li, Jing-yan; Yao, Ren-qi; Liu, Shuang-qing; Zhang, Yun-fei; Yao, Yong-ming; Tian, Ying-ping (Frontiers in Medicine, 2021)
Background: Sepsis is currently causing unpredictable harm and early identification of risk for mortality may be conductive to seasonably clinical diagnosis in septic patients. The present study proposed to assess the efficacy of monocyte/high-density lipoprotein (HDL) cholesterol ratio (MHR) combined with neutrophil/lymphocyte ratio (NLR) on the day of admission in predicting the 28-day mortality risk of patients with severe sepsis. Material and Methods: An observational and retrospective cohort research from a single-center was administrated by enrolling patients with sepsis. We collected clinical data including demographics, baseline characteristics, and larboratory results of these patients. The correlation of the clinical biomarkers (CRP, PCT, NLR, and MHR) together with system severity scores abbreviated as APACHE II as well as SOFA, were displayed by correlation analysis, and further Cox regression model was performed to screen the independently risk factors and estimate the capacity of multiple markers in predicting 28-day mortality. The receiver operating characteristic (ROC) curve was applied to calculate cut-off values for the diagnosis and prognostic risk, while the area under ROC curve (AUC) and net reclassification improvement index (NRI), as well as integrated discrimination improvement index (IDI) were employed to assess the feasibility of multi-biomarkers for predicting 28-day mortality of septic patients. Results: 274 eligible septic patients were enrolled in the current research. The correlation analysis indicated NLR and MHR were more closely related to the sepsis severity than indicators of PCT and CRP. A multivariate analysis in the Cox regressive model revealed that NLR and MHR were closely related to hospitalized death rate in patients with sepsis after adjusting for other potential confounders (NLR, odds ratio 1.404 [95% CI 1.170-1.684], P <0.001; MHR, odds ratio 1.217 [95% CI 1.112-1.331], P <0.001). The AUC of NLR, NLR_MHR was 0.827, 0.876, and 0.934, respectively. The addition biomarker of NLR_MHR to the prediction model significantly improved the IDI 18.5% and NRI 23.4%. Conclusions: Our findings suggested NLR and MHR trended a significantly elevated level in the non-survivor patients with sepsis. NLR_MHR, regarded to be an independent risk factor of increased mortality, might significantly improve the predictive value of 28-day mortality risk in septic patients.